Comparative Analysis of Potential Risk Factors for at-Risk Gambling, Problem Gambling and Gambling Disorder among Current Gamblers—Results of the Austrian Representative Survey 2015 - Buth, Sven; Wurst, Friedrich M.; Thon, Natasha; Lahusen, Harald; Kalke, Jens (Frontiers in Psychology, 2017)
Background: The risk of developing a problem gambling behaviour is distributed unequally among the population. For example, individuals who report stressful life events, show impairments of mental health or belong to a socio-economically deprived group are affected more frequently by gambling problems. The aim of our study is to investigate whether these risk factors are equally relevant for all gambling groups (social=0 DSM-5 criteria, at risk=1 DSM-5 criterion, problem=2-3 DSM-5 criteria, disordered=4-9 DSM-5 criteria). Methods: Of a total of 10,000 participants in the representative gambling survey in Austria in 2015, 4,082 individuals reported gambling during the last 12 months and were allocated to the four gambling groups according to DSM-5. With social gamblers as the reference group, relevant risk factors for the other three groups were identified by means of bi- and multivariate multinomial logistic regression. Results: Significant risk factors for gambling disorder are at-risk alcohol use (OR=4.9), poor mental health (OR=5.9), young age (<=26 years, OR=2.1), a low level of formal education (OR=2.4), having grown up with a single parent (OR=2.5), parents with addiction problems (OR=2.3) and belonging to the working class (OR=2.9). Risk factors for problem gambling are parents with addiction problems (OR=3.8), poor mental health (OR=2.6) and a young age (OR=2.2). With regard to at-risk gambling, only growing up with a single parent was relevant (OR=2.4). Conclusion: Overall, the results of this study suggest, that the number and the influence of the included risk factors differ between gambling problem groups. Apparently, the development of severe gambling problems is to a lesser extent facilitated by specific risk factors than by their cumulative presence. Therefore, future prevention and treatment measures should place a particular focus on individuals who have experienced growing up in a difficult family situation, have poor mental health, suffer from substance-related problems or have a low level of formal education.